El carácter estratégico de la proyección externa de la marca hospitalaria: el caso de Mayo Clinic - Medina Aguerrebere, Pablo (Universidad y Salud, 2012)
In hospitals, professional management of communication is not really established. However, hospitals have different tools of communication such as interpersonal, internal, corporate and marketing communication, which adjust to their needs. The professional management of this area brings several benefits to hospitals, but to do this, it is necessary that communication initiatives are geared to the construction of a strong hospital brand, whose external projection will allow the organization to establish good relations with each of its stakeholders and get different communicative and organizational benefits.